Social Prophetism in Fitri Merawati’s Poetic Texts - Risqi Kurniasih; Zahra Amanda Putri; Ilham Rabbani; Fatma Fadila; Mutiara Ayu Cahyaningtyas; Ayu Wandini (CV. Tripe Konsultan, 2026)
Literature within the constellation of modern civilization is compelled to assume a proactive role as an instrument of social enlightenment to address structural inequalities, moral crises, and the disorientation of national identity. This study aims to deconstruct and formulate the representation of social-prophetic ethics embedded in two contemporary poems by Fitri Merawati, titled “Wanita Utama” and “Di Balik Benteng.” This inquiry is firmly grounded in Kuntowijoyo’s prophetic literature framework, which positions literary works as catalysts for civilizational transformation through the pillars of humanization, liberation, and transcendence. A sociology of literature approach is comprehensively applied to dissect the sharp dialectic between poetic texts and the social problems entangling contemporary society. The analytical findings indicate that Fitri Merawati successfully converts her imaginative space into a platform for social critique and prophetic enlightenment. Both works position the female subject and the silence of spiritual practice as central forces in orchestrating a movement of social piety. At the level of humanization, the poetic texts dismantle public historical amnesia by revitalizing local traditions as a protective shield against the tides of mass dehumanization within the sphere of social interaction. On the axis of liberation, the texts expose the hegemony of structural oppression through cultural resistance strategies that operate in silence yet hold broad implications for the emancipation agenda. The entirety of the humanistic impetus and the endeavor for liberation is absolutely secured by the pillar of transcendence, wherein surrender is positioned as a moral anchor for creating a more equitable sociocultural system. The aesthetic construction in these verses proves that the social prophetism voiced by a female poet is capable of generating a deeply rooted model of cultural mission, while simultaneously transforming social despair into a persistent field of societal transformation.